The Beaker phenomenon and the genomic transformation of northwest Europe - Olalde, Iñigo; Brace, Selina; Allentoft, Morten E; Armit, Ian; Kristiansen, Kristian; Booth, Thomas; Rohland, Nadin; Mallick, Swapan; Szécsényi-Nagy, Anna; Mittnik, Alissa; Altena, Eveline; Lipson, Mark; et al. (Nature, 2018)
From around 2750 to 2500 bc, Bell Beaker pottery became widespread across western and central Europe, before it disappeared between 2200 and 1800 bc. The forces that propelled its expansion are a matter of long-standing debate, and there is support for both cultural diffusion and migration having a role in this process. Here we present genome-wide data from 400 Neolithic, Copper Age and Bronze Age Europeans, including 226 individuals associated with Beaker-complex artefacts. We detected limited genetic affinity between Beaker-complex-associated individuals from Iberia and central Europe, and thus exclude migration as an important mechanism of spread between these two regions. However, migration had a key role in the further dissemination of the Beaker complex. We document this phenomenon most clearly in Britain, where the spread of the Beaker complex introduced high levels of steppe-related ancestry and was associated with the replacement of approximately 90% of Britain's gene pool within a few hundred years, continuing the east-to-west expansion that had brought steppe-related ancestry into central and northern Europe over the previous centuries.
Keywords: DNA, Ancient; haplotypy; migrace lidstva; populační genetika; Male; Gene Pool; genom lidský; časoprostorová analýza; Genetics, Population; Europe; Chromosomes, Human, Y; Haplotypes; mužské pohlaví; Cultural Evolution; Genomics; Genome, Human; History, Ancient; Evropa; dějiny starověku; Human Migration; starobylá DNA; lidé; genový pool; Humans; kulturní evoluce; Spatio-Temporal Analysis; lidský chromozom Y; genomika